Inhibition of USP9X induces apoptosis in FLT3-ITD-positive AML cells cooperatively by inhibiting the mutant kinase through aggresomal translocation and inducing oxidative stress. (1st July 2019) - Akiyama, Hiroki; Umezawa, Yoshihiro; Ishida, Shinya; Okada, Keigo; Nogami, Ayako; Miura, Osamu
Abstract: FLT3-ITD and FLT3-TKD are the most frequent mutations in acute myeloid leukemia (AML) with the former associated with a poor prognosis. Here we show that inhibition of the deubiquitinase USP9X by its inhibitor WP1130 or EOAI3402143 (G9) induces apoptosis preferentially in cells transformed by these mutant kinases, including FLT3-ITD-positive AML cell line MV4-11 and primary AML cells. Mechanistically, WP1130 induced aggresomal translocation of the mutant kinases, particularly FLT3-ITD in its activated and autophosphorylated conformation, to block the downstream signaling events, which was aggravated by knock down of USP9X. Moreover, USP9X physically associated with FLT3-ITD to inhibit its K63-linked polyubiquitination, while FLT3-ITD induced tyrosine phosphorylation and degradation of USP9X through the ubiquitin/proteasome pathway. WP1130 or G9 also induced oxidative stress to stimulate stress-related MAP kinase pathways and DNA damage responses to activate in cooperation with inhibition of FLT3-ITD signaling the intrinsic mitochondria-mediated apoptotic pathway, which was synergistically enhanced by BH3 mimetics and prevented by overexpression of Bcl-xL or Mcl-1. Thus, USP9X represents a promising target for novel therapies against therapy-resistant FLT3-ITD-positive AML. Highlights: USP9X inhibitors preferentially induce apoptosis in AML cells with FLT3-ITD. Inhibition of USP9X induces aggresomal translocation of FLT3-ITD and oxidative stress. USP9X physically associates with FLT3-ITD to reduce K63-linked polyubiquitination. FLT3-ITD phosphorylates USP9X to enhance ubiquitination and proteasomal degradation. Mcl-1 is cleaved by caspases in AML cells with FLT3-ITD treated with USP9X inhibitors.